Die apokryph gewordenen Evangelien : Studien zu neuen Texten und zu neuen Fragen - Lührmann, Dieter. (Novum Testamentum, Supplements, 2004)
Known for his studies on the canonical gospels and on Paul, Dieter Lührmann has also done pioneering work on the apocryphal gospels. This volume presents his essays on new fragments of the gospels of Peter and Mary Magdalene, of the Egerton gospel and of the gospel according to the Hebrews. All essays have been revised and updated, and a new one on the gospel of Thomas in Greek has been added. The work is framed by new studies on the problematic claim for a canon, and on following in the footsteps of Jerome in modern scholarship, showing how deeply it has been inspired by his picture of the apocrypha.